2018
DOI: 10.1016/j.paid.2017.09.003
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between two types of reputational concern and altruistic behavior in daily life

Abstract: Although many studies have shown that reputational cues promote altruism, few studies have focused on individual differences. The present study provides novel evidence indicating that the relationship between reputational concern and altruistic behavior differs according to the type of reputational concern involved and the recipients of altruism. Specifically, the relationships between individual differences of two reputational concerns (i.e., praise seeking and rejection avoidance) and the frequency with whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 34 publications
2
11
1
Order By: Relevance
“…The present study found that the relationship between rejection avoidance and altruism was moderated by social norms; that is, people who fear rejection from others tend to inhibit altruism only when altruism was not perceived as normative. These findings contribute to explaining the results of previous study (Kawamura & Kusumi, 2018), which found that rejection avoidance is related to altruism toward strangers.…”
Section: Discussionsupporting
confidence: 86%
See 4 more Smart Citations
“…The present study found that the relationship between rejection avoidance and altruism was moderated by social norms; that is, people who fear rejection from others tend to inhibit altruism only when altruism was not perceived as normative. These findings contribute to explaining the results of previous study (Kawamura & Kusumi, 2018), which found that rejection avoidance is related to altruism toward strangers.…”
Section: Discussionsupporting
confidence: 86%
“…For example, Parks and Stone (2010) demonstrated that a person who excessively contributed more toward public goods than others was negatively evaluated by other group members. This finding is in line with Kawamura and Kusumi (2018) who measured altruism toward strangers, which is less normative compared to altruism toward more familiar recipients. Taken together these studies suggests that, when altruism is not evaluated as normative, people with high rejection avoidance may inhibit altruistic behavior in fear of possible negative evaluation from others.…”
Section: Introductionsupporting
confidence: 86%
See 3 more Smart Citations